Xanthomonas oryzae pv. oryzae avirulence genes contribute differently and specifically to pathogen aggressiveness - Bai, Jianfa; Choi, Seong-Ho; Ponciano, Grisel; Leung, Hei; Leach, Jan E. (Scientific Societies, 2000)
Genomic copies of three Xanthomonas oryzae pv. oryzae avirulence (avr) genes, avrXa7, avrXa10, and avrxa5, and four homologous genes, aB3.5, aB3.6, aB4.3, and aB4.5, were mutagenized individually or in combination to study the roles of avr genes in one component of pathogen fitness, i.e., aggressiveness or the amount of disease X. oryzae pv. oryzae causes in susceptible rice lines. These X. oryzae pv. oryzae genes are members of the highly related Xanthomonas avrBs3 gene family. Compared to the wild-type strain, X. oryzae pv. oryzae strains with mutations in avrXa7, avrxa5, and the four homologous genes caused shorter lesions on rice line IR24, which contains no resistance genes relevant to the wild-type strain. The contribution of each gene to lesion length varied, with avrXa7 contributing the most and avrXa10 showing no measurable effect on aggressiveness. The functional, plasmidborne copies of avrXa7, aB4.5, and avrxa5 restored aggressiveness only to strains with mutations in avrXa7, aB4.5, and avrxa5, respectively. Mutations in avrXa7 were not complemented by plasmids carrying any other avr gene family members. These data indicate that some, but not all, avr family members contribute to pathogen aggressiveness and that the contributions are quantitatively different. Furthermore, despite their sequence similarity, the aggressiveness functions of these gene family members are not interchangeable. The results suggest that selection and pyramiding resistance genes can be guided by the degree of fitness penalty that is empirically determined in avr gene mutations.